Oil multinationals and governments in post-colonial transitions: Burmah Shell, the Burmah Oil Company and the Indian state 1947–70. Issue 3 (3rd April 2017) - Verma, Shraddha; Abdelrehim, Neveen
Abstract: Using the post-colonial perspective of hybridity, this article analyses how two British companies, the Burmah Oil Company (BOC) and Burmah Shell (BS) adapted to changes in the socio-economic environment from Indian independence in 1947 until 1970. Post-colonial theory is useful in exploring the continuing imperial influence, the changing relationship between BS, BOC and the Government of India (GOI) and the impact of this on the operations of BOC and BS post-independence. The approach recognises that the relationship between BOC, BS and the GOI was complex with differing levels of co-operation and tension existing between the three parties throughout the period.